Non-linear unit root properties of stock prices : evidence from India, Pakistan and Sri Lanka. - Tan, Siow Hooi; Habibullah, Muzafar Shah; Khong, R. W. L. (Economics Bulletin, 2010)
This study applies a threshold autoregressive (TAR) model to monthly stock prices for three South Asian countries over the period from 1991:01 to 2009:09. Two main conclusions are drawn. Firstly, the results indicate that all the stock prices in this study exhibit non-linear behavior. Secondly, a partial unit root was found to be present in one of the regimes indicating that the stock prices are weak form efficiency, but not all the time.